2013
DOI: 10.1074/jbc.m112.398875
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor (TLR) 2 Mediates Inflammatory Responses to Oligomerized RrgA Pneumococcal Pilus Type 1 Protein

Abstract: Background:The pneumococcal pilus is associated with increased inflammation. Results: A 49-amino acid region of the pilus protein RrgA activates TLR2 and is associated with increased inflammation and virulence. Conclusion:The pneumococcal pilus is a TLR2 agonist; RrgA is a key component. Significance: A better understanding of the pilus in bacterial pathogenesis is crucial for the development of novel strategies against this pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 51 publications
3
34
1
Order By: Relevance
“…It is widely accepted that LPS from Gram-negative bacteria is recognized by TLR4 (44) and that peptidoglycan, teichoic acid, and lipoprotein are recognized by TLR2 (45)(46)(47). In the context of Streptococcus pneumoniae, some virulence proteins (RrgA pneumococcal pilus type 1 protein, GHIP, et al) bind to TLR2 (48,49) and Ply binds to TLR4 (50). Our results demonstrated that PepO-induced miR-155 upregulation relied on TLR2.…”
Section: Discussionmentioning
confidence: 60%
“…It is widely accepted that LPS from Gram-negative bacteria is recognized by TLR4 (44) and that peptidoglycan, teichoic acid, and lipoprotein are recognized by TLR2 (45)(46)(47). In the context of Streptococcus pneumoniae, some virulence proteins (RrgA pneumococcal pilus type 1 protein, GHIP, et al) bind to TLR2 (48,49) and Ply binds to TLR4 (50). Our results demonstrated that PepO-induced miR-155 upregulation relied on TLR2.…”
Section: Discussionmentioning
confidence: 60%
“…Among the PRRs, TLR2 has specificity for a structurally diverse repertoire of MAMPs (i.e., peptidoglycan, lipoteichoic acid, and lipoprotein) in Gram-positive bacteria, which functionally is reliant on heterodimer formation with either TLR1 or TLR6 [13], [38]. Interestingly, a quite recent study has now demonstrated that the type 1 pilus from Streptococcus pneumoniae is a TLR2 agonist and can be considered an important determinant for TLR2-dependent induction by this particular Gram-positive pathogen [39]. Similarly, it has recently been inferred that the SpaCBA pilus in L. rhamnosus GG might be a determining factor that helps this bacterium trigger TLR2-activated NF-κB responses [28].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also shown that TLR2 plays a very important role in inflammatory responses by regulating MyD88, leading to the activation of MAPKs and NF-κB and the subsequent production of pro-inflammatory cytokines [29] . MyD88 is a signaling adaptor protein that is critical in the immune response against a wide range of microbial pathogens [30] and is necessary for the phosphorylation and activation of IRAK1 through the recruitment of IRAK4 [31] .…”
Section: Discussionmentioning
confidence: 99%